Africa's new peace and security architecture promoting norms, institutionalizing solutions - Engel, Ulf; Porto, Joao Gomes (Global security in a changing world, 2010)
This volume offers an informed and critical analysis of the operationalization and institutionalization of the peace and security architecture by the African Union and Africa's Regional Economic Communities (RECs). It examines the institutions that will carry the mandate forward.